PLACE AND ROLE OF MARKETING COMMUNICATION IN RURAL AREAS IN CENTRAL SERBIA - Dašić, Dejan; Vitković, Biljana; Ilievska Kostadinović, Marija; Kostadinović, Gruja; Ratković, Milijanka (Economics of Agriculture, 2024)
Social media is a new emerging field in agricultural marketing, and its use is rapidly evolving, upgrading, and expanding. The aim of this study is to determine the attitudes of agricultural product producers in central Serbia regarding the use of social media in their business, with a focus on identifying the perception of the promotional potential of social networks themselves. The research included a final sample of 200 respondents. The basic hypothesis in this paper is that the internet as a technology for e-commerce, information, and advertising has great potential to improve the position of farmers and producers, but it is not fully utilized. The majority of agricultural producers still use Facebook as one of the main promotional channels.